Jackfruit Seed Powder – A Healthy Nutritional Alternative to Flours (Bangladesh Journal of Nutrition, 2020)
Jackfruit (Artocarpusheterophyllus Lam.), widely grown in South Asian countriesis the national fruit of Bangladesh. The objective of the study is to compare some Results: physicochemical properties and nutritional parameters of five types of grain flours to that of jackfruit seed powder from Bangladeshi origin. We have analyzed the mineral contents of all these flours in Atomic Absorption Spectrophotometer. Vitamin A and Vitamin C were measured in UV spectrophotometry. Riboflavine and Thiamine contents were determined in the flours in High Performance Liquid Chromatography method. The nutrient content in five types of flours have also been analyzed to see whether there is any difference in them at significance level of 5% ( P